To calculate each of these values, we substitute the respective values of x into the function f(x).
1. f(-1):
Since x = -1 is less than 0, we will use the first part of the function.
f(-1) = 6(-1) + 9
f(-1) = -6 + 9
f(-1) = 3
2. f(0):
Since x = 0, we will use the second part of the function.
f(0) = 6(0) + 18
f(0) = 0 + 18
f(0) = 18
3. f(2):
Since x = 2 is greater than or equal to 0, we will use the second part of the function.
f(2) = 6(2) + 18
f(2) = 12 + 18
f(2) = 30
Therefore, the values are:
f(-1) = 3
f(0) = 18
f(2) = 30
f(x)={6x+9 x<0
6x+18 x>=0
Calculate the following values:
f(-1)
f(0)=
f(2)=
1 answer